2021
DOI: 10.3390/foods10112666
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Dietary Polyphenols: The Role in LDL-C Lowering

Abstract: Cardiovascular diseases are the leading causes of the death around the world. An elevation of the low-density lipoprotein cholesterol (LDL-C) level is one of the most important risk factors for cardiovascular diseases. To achieve optimal plasma LDL-C levels, clinal therapies were investigated which targeted different metabolism pathways. However, some therapies also caused various adverse effects. Thus, there is a need for new treatment options and/or combination therapies to inhibit the LDL-C level. Dietary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 240 publications
(202 reference statements)
1
15
0
Order By: Relevance
“…Several dietary compounds could have cholesterol lowering effect. Such dietary compounds include oat/barley β-glucans [ 127 , 128 ], plant sterols/stanols [ 129 , 130 ], omega-3 fatty acids [ 131 , 132 ], polyphenols [ 133 , 134 ], and soy proteins [ 135 , 136 , 137 , 138 ]. In addition to cholesterol lowering effects, dietary molecules potentially have immunomodulatory effects.…”
Section: Cholesterol Lowering Dietary Compoundsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several dietary compounds could have cholesterol lowering effect. Such dietary compounds include oat/barley β-glucans [ 127 , 128 ], plant sterols/stanols [ 129 , 130 ], omega-3 fatty acids [ 131 , 132 ], polyphenols [ 133 , 134 ], and soy proteins [ 135 , 136 , 137 , 138 ]. In addition to cholesterol lowering effects, dietary molecules potentially have immunomodulatory effects.…”
Section: Cholesterol Lowering Dietary Compoundsmentioning
confidence: 99%
“…Polyphenols are secondary metabolites containing one or more hydroxyl groups. Studies have shown that many polyphenols such as catechins, gallic acid, quercetin, chlorogenic acid, curcumin, and resveratrol, lower cholesterol levels in mice and in cultured cells in vitro [ 133 , 134 ].…”
Section: Cholesterol Lowering Dietary Compoundsmentioning
confidence: 99%
See 3 more Smart Citations